Naringenin Enhances the Anti-Tumor Effect of Doxorubicin on HeLa Cervical Cancer Cells Through Cytotoxic Activity and Apoptosis Induction - Larasati, .; Kusharyanti, Indri; Hermawan, Adam; Susidarti, Ratna Asmah; Meiyanto, Edy (Indonesian Research Gateway, 2011)
Naringenin, an abundant flavanon in the peel of citrus fruits is reported to possess anti-proliferative effect in many cancer cells. Herein, we investigated the cytotoxic effect and apoptosis induction of naringenin in combination with doxorubicin on HeLa cells. The cytotoxicity assay of naringenin, doxorubicin, and their combination were carried out by using MTT assay. Cell viability was used as the parameters to evaluate combination effectiveness. Cell cycle distribution was determined by flow cytometry and analyzed using ModFit LT 3.0 program. Apoptosic assay was done by double staining method using Ethidium Bromide-Acridine Orange. Investigation on the expression of Bax and Bcl-2 were determined by immunocytochemistry method. Naringenin and doxorubicin showed cytotoxic effect on HeLa cells with their IC50 values of 195 µM and 1 µM, respectively. Whereas combination of naringenin - doxorubicin showed greater cytotoxicity compared the single treatment of doxorubicin. The strongest cytotoxic activity was observed at a combination of 100 µM naringenin and 0,5 µM doxorubicin. Single treatment of 0,5 µM doxorubicin for 24 hours on HeLa cells induced S-phase arrest while 100 µM naringenin did not affect on HeLa cell cycle. The combination induced S-phase arrest with the increased of sub-G1 phase percentage. In accordance with the flow cytometry results, the double staining apoptosis assay results showed the increase of apoptotic cells. Naringenin, doxorubicin, and their combination also increased the expression of Bax and decreased the expression of Bcl-2. These results concluded that naringenin was a potential co-chemotherapy agent for cervical cancer due to its synergism with doxorubicin.Keywords: co-chemotherapy, naringenin, doxorubicin, HeLa cells, cytotoxicity, cell cycle, apoptosis